Efektivitas Logo Terapi Kelompok dalam Menurunkan Gejala Kecemasan pada Narapidana - Hardiyanti Rahmah; Nida Hasanati (JIP (Jurnal Intervensi Psikologi), 2016)
The aim of this study is to find out the effectiveness of group logotherapy in reducing prisoner anxiety symptom. There were five prisoners who will be free, but had an anxiety problem. They conducted group logotherapy that consist of six session treatments. Data was collected by interview, observation, and anxiety questioner HARS. Data analysis showed that anxiety, decrease after intervention was delivered. Key words: group logotherapy, anxiety, prisoner